5.3+z=-9

Simple and best practice solution for 5.3+z=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.3+z=-9 equation:


Simplifying
5.3 + z = -9

Solving
5.3 + z = -9

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5.3' to each side of the equation.
5.3 + -5.3 + z = -9 + -5.3

Combine like terms: 5.3 + -5.3 = 0.0
0.0 + z = -9 + -5.3
z = -9 + -5.3

Combine like terms: -9 + -5.3 = -14.3
z = -14.3

Simplifying
z = -14.3

See similar equations:

| 25.61+4.1= | | 3(w-3)=w+4-5(-2w-1) | | -2(3Z-5)+7(z-7)=-13-6 | | 9x^4-66x^2+121=0 | | 25r-25r+25r=5-2.5r | | n+6=96 | | -(y+15)+2y-12=-27 | | x^4-x^2=47x^2+49 | | -3(3u-1)+5u=9+4(2u-4) | | (7r^3-6r-6)(2r-4)= | | 62(x+20)=90 | | -(y+15)+2y-12=-42 | | t^3-10t+21=0 | | 9(s+6)-8s=45 | | 12x+11=13x+9 | | 4(8)+3y=35 | | 16t^2-96t-12=152 | | -1.8-3=7w-5.5-6w | | 12-40= | | 16-(2m+8)=4+3m-11 | | 4(w-5)-6=-4(-4w+9)-6w | | -10-6p+7p=-9 | | -21x-63=-126 | | 3x/4x-5/6=2x/3x | | 8s-4-7s=2-1 | | -0.53k=3.498 | | 16t^2-96t-4=144 | | 3x^2+18x=8 | | 3x(2x+10)=-24 | | m^2+(m-6)m= | | 12x+2=13x+9 | | 4r+3=r+27 |

Equations solver categories